Pengaruh Penggunaan Media Spinning Whell terhadap Pembelajaran Sejarah Kelas XI IPS SMA Negeri 3 Payakumbuh - Novalia, Indri; Meri, Destel; Yuhasnil, Yuhasnil; Asmara, Dedi (JOEAI (Journal of Education and Instruction), 2024)
This research is motivated by the lack of creative thinking skills of students when the teaching and learning process is in progress. This is caused by the lack of varied methods and use of media in learning which makes students passive when learning so that it has an impact on student learning outcomes. Based on this background, this study aims to determine the effect of using spinning wheel media on students' creative thinking abilities in history learning class XI Social Studies SMA Negeri 3 Payakumbuh. This research is an experimental research with Nonequivalent Control Group Design. The population of this research is students of class XI Social Studies SMA Negeri 3 Payakumbuh which has 4 classes. The sample of this study were 2 classes, namely XI IPS 2 as the experimental class and XI IPS 1 class as the control class. The data taken in this study are the social studies learning outcomes of the two sample classes. The data were analyzed with the similarity test of two averages (t-test), by first carrying out the normality test and homogeneity test. Based on the data analysis test with a confidence level of 95% (α = 0.05), then tcount = 6.08 and ttable 1.68. Because tcount > ttable means H0 is rejected and H1 is accepted. It can be seen from the results of the hypothesis test that the average value of the experimental class was 81.59 while the average control class was 70.69, thus there was an effect of using spinning whell media on students' creative thinking skills in history learning class XI Social Sciences SMA Negeri 3 Payakumbuh.